Cryptosporidium myocastoris n. sp. (Apicomplexa: Cryptosporidiidae), the Species Adapted to the Nutria (Myocastor coypus) - Ježková, Jana; Limpouchová, Zlata; Prediger, Jitka; Holubová, Nikola; Sak, Bohumil; Konečný, Roman; Květoňová, Dana; Hlásková, Lenka; Rost, Michael; McEvoy, John; Rajský, Dušan; Feng, Yaoyu; et al. (Microorganisms, 2021)
Cryptosporidium spp., common parasites of vertebrates, remain poorly studied in wildlife. This study describes the novel Cryptosporidium species adapted to nutrias (Myocastor coypus). A total of 150 faecal samples of feral nutria were collected from locations in the Czech Republic and Slovakia and examined for Cryptosporidium spp. oocysts and specific DNA at the SSU, actin, HSP70, and gp60 loci. Molecular analyses revealed the presence of C. parvum (n = 1), C. ubiquitum subtype family XIId (n = 5) and Cryptosporidium myocastoris n. sp. XXIIa (n = 2), and XXIIb (n = 3). Only nutrias positive for C. myocastoris shed microscopically detectable oocysts, which measured 4.8-5.2 × 4.7-5.0 µm, and oocysts were infectious for experimentally infected nutrias with a prepatent period of 5-6 days, although not for mice, gerbils, or chickens. The infection was localised in jejunum and ileum without observable macroscopic changes. The microvilli adjacent to attached stages responded by elongating. Clinical signs were not observed in naturally or experimentally infected nutrias. Phylogenetic analyses at SSU, actin, and HSP70 loci demonstrated that C. myocastoris n. sp. is distinct from other valid Cryptosporidium species.
Keywords: parasite; adaptation; prevalence; phylogeny; biology; course of infection; oocyst size; infectivity